2019
DOI: 10.1002/anie.201814340
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Construction of α‐Chiral Silanes by Nickel‐Catalyzed C(sp3)−C(sp3) Cross‐Coupling

Abstract: An enantioselective C(sp 3 ) À C(sp 3 )cross-coupling of racemic a-silylated alkyl iodides and alkylzinc reagents is reported. The reaction is catalyzedb yN iCl 2 /(S,S)-Bn-Pybox and yields a-chiral silanes with high enantiocontrol. The catalyst system does not promote the cross-coupling of the corresponding carbon analogue,c orroborating the stabilizing effect of the silyl group on the alkyl radical intermediate (asilicon effect). Both coupling partners can be,but do not need to be,functionalized, and hence,e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 50 publications
0
19
0
3
Order By: Relevance
“…[12] Applying these optimized conditions to av ariety of different carboxylic acid pairs demonstrated that the chemistry was useful for the synthesis of dialkyl ketones and aryl alkyl ketones (Table 2). Functional group compatibility included acidic NÀHbonds (14,15,16,35), protected nitrogen atoms (6,13,23,32), and protected alcohols (37, 39). Notably, ap rimary alkyl bromide (9)d id not react with nickel or the nucleophiles present.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[12] Applying these optimized conditions to av ariety of different carboxylic acid pairs demonstrated that the chemistry was useful for the synthesis of dialkyl ketones and aryl alkyl ketones (Table 2). Functional group compatibility included acidic NÀHbonds (14,15,16,35), protected nitrogen atoms (6,13,23,32), and protected alcohols (37, 39). Notably, ap rimary alkyl bromide (9)d id not react with nickel or the nucleophiles present.…”
mentioning
confidence: 99%
“…First, while most thioester substrates tested coupled in reasonable yield, reactions with thioesters derived from a-amino acids and 2-picolinic acid were low-yielding.Second, most N-hydroxyphthalimide esters coupled in high yield, but reactions with esters derived from secondary cyclopropyl carboxylic acids,d ifluoroacetic acid, and unstrained tertiary carboxylic acids (such as pivalic acid) were low-yielding.T he secondary cyclopropane limitation could be overcome with the use of an a-silyl group (29), which is easily introduced and removed. [15] Theu se of two different carboxylic acids instead of ac arboxylic acid and an alkyl halide or organometallic reagent has several notable advantages.F irst, the large number of carboxylic acids makes new chemical space available:( À)-menthyloxyacetic acid (12), a-amino acids (13,14,15), lithocholic acid (35), and 2,4-D (38)a re readily available as carboxylic acids,b ut their corresponding alkyl halides are not commercially available.Inthe cases where the corresponding alkyl bromides are available,t he cost difference can be significant (greater than 10-fold for 32, 34, see the Supporting Information). Second, because two acids are used, the mode of activation can be swapped to improve yields with little extra synthetic effort (Scheme 2): cyclopropane and adamantane carboxylic acids were best coupled as thioesters (25, 33)and a-amino acid NHP esters provided the best yields (13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note here that α-halo alkylboronates and alkylsilanes were capable of engaging in nickel-catalyzed enantioselective alkyl–alkyl Negishi coupling with alkylzinc bromides, therefore providing fully alkyl-substituted α-chiral boronates and silanes that are of value but were previously unavailable. 158 160 …”
Section: Cross-coupling Reactionsmentioning
confidence: 99%
“…[2,6] Our efforts to render these radical reactions enantioconvergent have been fruitless so far. [7] We therefore turned away from alkyl halides and redox-active carboxylic acid derivatives and considered the use of quaternary ammonium salts as electrophiles. [8] These are stable towards light and oxygen and easily accessible in high enantiomeric purity.…”
mentioning
confidence: 99%